Therapeutic Upper Gastrointestinal Endoscopy in Pediatric Gastroenterology - Schluckebier, Dominique; Afzal, Nadeem Ahmad; Thomson, Mike (Frontiers in Pediatrics, 2022)
This Chapter seeks to give a broad overview of paediatric upper GI pathologies we are now able to treat endoscopically, acquired or congenital, and we hope delivers the reader an impression of what is increasingly available to the pediatric endoscopist and their patients.